The Economic Performance Index (EPI) : an Intuitive Indicator for Assessing a Country's Economic Performance Dynamics in an Historical Perspective - Khramov, Vadim (IMF Working Papers; Working Paper ;, 2013)
Existing economic indicators and indexes assess economic activity but no single indicator measures the general macro-economic performance of a nation, state, or region in a methodologically simple and intuitive way. This paper proposes a simple, yet informative metric called the Economic Performance Index (EPI). The EPI represents a step toward clarity, by combining data on inflation, unemployment, government deficit, and GDP growth into a single indicator. In contrast to other indexes, the EPI does not use complicated mathematical procedures but was designed for simplicity, making it easier for professionals and laypeople alike to understand and apply to the economy. To maximize ease of understanding, we adopt a descriptive grading system. In addition to a Raw EPI that gives equal weights to its components, we construct a Weighted EPI and show that both indexes perform similarly for U.S. data. To demonstrate the validity of the EPI, we conduct a review of U.S. history from 1790 to 2012. We show that the EPI reflects the major events in U.S. history, including wars, periods of economic prosperity and booms, along with economic depressions, recessions, and even panics. Furthermore, the EPI not only captures official recessions over the past century but also allows for measuring and comparing their relative severity. Even though the EPI is simple by its construction, we show that its dynamics are similar to those of the Chicago Fed National Activity Index (CFNAI) and The Conference Board Coincident Economic Indexi (CEI).